Efeito químico de aditivos em suspensões aquosas de magnésia para potenciais aplicações em concretos refratários - Santos, Ana Maria dos (2015)
Magnesium oxide is an important subject of investigation because of its physical and chemical properties, mainly for its application to refractory ceramics. However, magnesium oxide hydration generates its hydroxide, Mg(OH)2, which may cause a volumetric expansion, possibly tightening and damaging components made from this material. These factors are limiting for the use in refractory castables and, as a result, most studies regarding this application is focused on minimizing its harmful effects. In order to minimize the effects of hydration on refractory compositions, this work evaluated two types of magnesia presenting different reactivity, caustic and sinter magnesia, with additives (CaCl2, MgCl2, CaF2, MgF2, acetic acid, magnesium acetate, citric acid and EDTA). The results indicated that the soluble salts (CaCl2 and MgCl2) accelerated the hydration, diminishing the apparent volumetric expansion, increasing the mechanical strength and the hydration heat. Because the addition of insoluble salts (CaF2, MgF2) promoted a reduction in the hydration degree, however, samples showed cracks, became crispy, and presented low mechanical strength. In the case of adding acetic acid or magnesium acetate, it occurred a precipitation acceleration of brucite, Mg (OH)2, as a result of the acetate ion complexation power generated, being mechanical resistance of the acetate greater than the acetic acid. The chelating agents (citric acid and EDTA) had distinct behaviors: the citric acid caused hydration decrease because of the absorption effect; and EDTA caused hydration increase as a result of its Mg2+ ions complexation power. It may be concluded that additives, presented in the compositions studied herein, are promising materials for refractory application, assuming that the additives hydrating will improve refractories mechanical strength, and those decreasing the hydration must be incorporated to other materials to improve their performance.